Statistical applications from clinical trials and personalized medicine to finance and business analytics : selected papers from the 2015 ICSA/Graybill Applied Statistics Symposium, Colorado State University, Fort Collins /: selected papers from the 2015 ICSA/Graybill Applied Statistics Symposium, Colorado State University, Fort Collins. (2016) - Unknown
No abstract available